Bonding Behavior of Brazing Al2O3 / ZrO2 Composite to Kovar Alloy - Jumah, Thamir A (Al-Nahrain Journal of Science, 2018)
The production of a reliable joint between alumina composite and kovar alloy by brazing technique using an active filler foil consist of (Ag 70%wt., Cu 28%wt., and Ti 2%wt.). Decontamination processes were achieved over all research specimens. Wetting and bonding behavior were attempted at different condition. Active filler is well brazed with the kovar alloy where the Young angle is (33), while poor wettable achievement appear on the ceramics surfaces where the values of Young angle are between (70 ) to (80 ). Good bonding obtained with the assembly of (K / 2a / AZ15) where the optimum bonding strength obtained is (90 Mpa), and the fracture occurred from the ceramic and ceramic – filler interface. New structural phases are established at the interlayer of bonded area when subjected to the XRD technique. The new phases enhancement the bonding strength of the kovar bonded alumina composite. The fractured area was subjected to the test of SEM technique then notice the active filler was diffused into alumina composite. This phenomenon gives indicate that the reliable joint was due to the diffusivity of active filler into alumina composite and then enhanced the joint strength.